2007
DOI: 10.1242/dev.02840
|View full text |Cite
|
Sign up to set email alerts
|

Protease nexin 1 and its receptor LRP modulate SHH signalling during cerebellar development

Abstract: Development of the postnatal cerebellum relies on the tight regulation of cell number by morphogens that control the balance between cell proliferation, survival and differentiation. Here, we analyze the role of the serine-protease inhibitor protease nexin 1 (PN-1; SERPINE2) in the proliferation and differentiation of cerebellar granular neuron precursors (CGNPs) via the modulation of their main mitogenic factor, sonic hedgehog (SHH). Our studies show that PN-1 interacts with low-density lipoprotein receptorre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…The finding that the transcription of two Xenopus PN1 homeologs is positively regulated by FGF signals is consistent with previous reports that FGF2 stimulates murine PN1 expression in primary mid/hindbrain and cultured cerebellum cells (Küry et al, 1997;Vaillant et al, 2007), supporting the contention that PN1 might be an FGF target gene. PN1 is a member of the serpin family of serine protease inhibitors, with an RCL that participates in an unusual non-covalent binding to the proteolytic trypsin domain of HtrA1.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding that the transcription of two Xenopus PN1 homeologs is positively regulated by FGF signals is consistent with previous reports that FGF2 stimulates murine PN1 expression in primary mid/hindbrain and cultured cerebellum cells (Küry et al, 1997;Vaillant et al, 2007), supporting the contention that PN1 might be an FGF target gene. PN1 is a member of the serpin family of serine protease inhibitors, with an RCL that participates in an unusual non-covalent binding to the proteolytic trypsin domain of HtrA1.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations that PN1 negatively regulates FGF signals and stabilizes Sdc4 protein in an HtrA1-dependent manner are consistent with a possible indirect inhibition of zygotic Wnt/β-catenin signaling by PN1. In mouse, PN1 inhibits Shh signaling in the postnatal cerebellum and in prostate cancer (Vaillant et al, 2007;McKee et al, 2012). However, Hh antagonism is unlikely to explain the PN1 activities described here because Hh signals do not induce mesoderm and -similar to PN1 -inhibit neuronal differentiation and promote anterior development in the early Xenopus embryo (Lai et al, 1995;Franco et al, 1999;Min et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As a glia-derived nexin, SERPINE2 is involved in regulating astrocyte proliferation, neurite outgrowth, neuron migration and localization, contributing to the development of brain, and the regeneration and reconstruction of neurons (38)(39)(40)(41). Our studies of EST profile showed that SERPINE2 expression begins to climb at early as the fetus stage, reaches a peak at the neonate and plateaus after the juvenile stage (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The increased expression of SERPINE2 in the neonate stage with the remarkable development of nervous systems annouces its potential role in nervous system development. Indeed, SERPINE2 may contribute to the development of the brain by modulating the proliferation and differentiation of cerebellar granular neuron precursors via the major mitogen SHH, as well as via granule neuron migration and positioning (41). SERPINE2 may exert protective activity in the pathalogical progression of intracranial hemorrhage (42), cerebral ischemia (40), and Alzheimer's disease (43).…”
Section: Discussionmentioning
confidence: 99%